STRATEGI INTEGRATED MARKETING COMMUNICATION DALAM PENINGKATAN BRAND AWARENESS - Desy Satriana Anas (Ikon --Jurnal Ilmiah Ilmu Komunikasi, 2021)
Research background with the existence of business in the field of services, especially education services, Campus Y.A.I is a campus that brings the concept of a campus strategic location and affordable cost. This study aims to determine the integratred marketing communication strategy in increasing brand awareness in the Higher Education Institution Y.A.I or more familiar with campus Y.A.I. The theory used in this research is PENCIL communication strategy theory with Integrated Marketing Comunications implementation, that is using promotion mix concept, so that there will be an increase of brand awareness on Y.A.I campus. This type of this research is qualitative descriptive, with the object of research is integratred marketing communication strategy in increasing brand awareness in Higher Education Institution Y.A.I. The key informant in this research is Sdri. Maya as the coordinator of promotion and marketing in the division of Public Relations and Marketing Y.A.I and informants in this research there are 5 people including Djodi, Tomi, Septika, Mira, Wimpi with different backgrounds. The results of this study indicate that integarated marketing communications strategy using promotion mix concept (advertising, public relations, sales promotion, personal selling, and direct marketing) is quite successful, so that brand awareness happens to consumer stage of consumer remember the brand. The conclusion that has been in this research is YAI Campus, is successful in using integrated marketing communications as a strategy in marketing its promotional mix concepts used are advertising, public relations, sales promotion, personal selling, and direct marketing, but for the future is expected to plan in making IMC strategy better yet for the results obtained can reach at the level of top of mind.